Peran Moderasi Profitabilitas Terhadap Faktor Prediksi Financial Distress - Ma’rufatur Rodhiyah; Irma Indira; Aranta Prista Dilasari (Jurnal Manajemen Riset Inovasi, 2023)
Financial distress is a condition whene the company are in a state financial difficultes. Every company must have an early an early warning system to detect the potential for financial distress in order to avoid bankruptcky. The Purpose of this is to analyze and provide empirical evidence regarding the effect profitability (ROA), as a moderating between liquidity (CR), leverage (DAR), sales gowth (SG), in predicting financial distress (Altman Z-Score). The population in this purpose were retail companies on the IDX for the 2016-2020 period, with a sample of 19 companies studied for 5 years so that 95 samples were obtained, using the purposive sampling method. The data used is secondary data in the form of information from the company’s financial statements. The data analysis technique used logistic regression and moderating regretion analysis (MRA). The rsults prove that the variables of liquidity, sales growth and profitability are able to predict financial distress, while leverage cannot predict financial distress, the profitability variable strengthens the influence of liquidity and sales growth in predicting financial distress but weakens leverage in predicting financial distress. The advince given is expected thet the company can increase the effectiveness and efficiency in managing assets and can increase sales so that the profit received by the company increases so that the company can avoid financial distress.